2021
DOI: 10.1016/j.physio.2021.01.002
|View full text |Cite
|
Sign up to set email alerts
|

Current practice and barriers to ICU-acquired weakness assessment: a cross-sectional survey

Abstract: This is a PDF file of an article that has undergone enhancements after acceptance, such as the addition of a cover page and metadata, and formatting for readability, but it is not yet the definitive version of record. This version will undergo additional copyediting, typesetting and review before it is published in its final form, but we are providing this version to give early visibility of the article. Please note that, during the production process, errors may be discovered which could affect the content, a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
12
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(12 citation statements)
references
References 18 publications
0
12
0
Order By: Relevance
“…Ongoing education and training teach ICU nurses to promptly identify patient problems or abnormal changes by evaluating data, clarifying relevant influencing factors, and detecting potential risk factors and health problems early (Wibrandt & Lippert, 2020). Wu et al (2021) and Allen (2020) reported that insufficient ICU nursing knowledge can lead to complications or patient death, so proper and complete ICU nursing skills are necessary and important for patient safety. Wei et al (2019) pointed out that the clinical abilities of ICU nurses vary greatly, and ICU work experience is closely related to individual ICU nursing ability.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Ongoing education and training teach ICU nurses to promptly identify patient problems or abnormal changes by evaluating data, clarifying relevant influencing factors, and detecting potential risk factors and health problems early (Wibrandt & Lippert, 2020). Wu et al (2021) and Allen (2020) reported that insufficient ICU nursing knowledge can lead to complications or patient death, so proper and complete ICU nursing skills are necessary and important for patient safety. Wei et al (2019) pointed out that the clinical abilities of ICU nurses vary greatly, and ICU work experience is closely related to individual ICU nursing ability.…”
Section: Discussionmentioning
confidence: 99%
“…In previous studies, Wu et al (2021) and Pronovost et al (2006) proposed the following reasons for incomplete care by ICU nurses: insufficient critical thinking, inadequate performance of critical care assessments, incompetence, lack of relevant on-the-job education, reliance on personal experience, and inconsistent evaluations.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Evidence [20] suggests that highly educated people are more inquisitive compared to others, more adept at predicting the precursors of defending the conditions of critically ill children, and analyzing and summarizing the various problems arising in clinical work. Further, individuals with high education levels also have a good level of scienti c thinking ability to access relevant information, as well as understand and seek solutions.…”
Section: Overall Evaluation Of Kap Regarding Children With Icu-awmentioning
confidence: 99%
“…Mechanical ventilation (MV) is associated with many complications including ventilator-associated pneumonia, ventilator-associated lung injury, and ICU-acquired weakness [1][2][3]. Once the cause that lead to respiratory insu ciency is reversed, patient should be weaned from MV as it imposes a series of risks.…”
Section: Introductionmentioning
confidence: 99%